Engineered neutrophil membrane-camouflaged nanocomplexes for targeted siRNA delivery against myocardial ischemia reperfusion injury - Yaohui Jiang; Rongyan Jiang; Zequn Xia; Meng Guo; Yanan Fu; Xiaocheng Wang; Jun Xie (Journal of Nanobiotechnology)
Abstract Small interfering RNA (siRNA) therapies hold great potential for treating myocardial ischemia-reperfusion injury (MIRI); while their practical application is limited by the low bioavailability, off-target effects, and poor therapeutic efficacy. Here, we present an innovative engineered neutrophil membrane-camouflaged nanocomplex for targeted siRNA delivery and effective MIRI therapy. A nanoparticle (NP)-based siRNA delivery system, namely MNM/siRNA NPs, is camouflaged with neutrophil membranes modified by hemagglutinin (HA) and integrins. Our comprehensive in vitro studies show that MNM/siRNA NPs effectively facilitate endosomal escape through HA, achieve excellent targeting via integrins, and significantly reduce integrin α9 expression. Furthermore, in MIRI mice, we identify integrin α9 as a potential target for MIRI therapy and demonstrate that MNM/siRNA NPs significantly decrease myocardial infarction area and improve cardiac function by reducing neutrophil recruitment, neutrophil extracellular trap (NET) and microthrombus formation. These findings highlight the engineered membrane-camouflaged NPs as a promising siRNA delivery platform, offering an effective treatment strategy for MIRI.